The dollar/euro exchange rate and a comparison of major models - Hsing, Yu; Sergi, Bruno S. (Journal of Business Economics and Management, 2010)
This article analyzes the behaviour of the USD/EUR exchange rate based on four major models. Using the mean absolute percent error (MAPE) as a criterion, the extended Mundell‐Fleming model performs best, followed by the PPP model using the relative PPI, the monetary model, the PPP model using the relative CPI, and the UIP model. The widely used log‐log form in the PPP model based on the relative PPI or CPI can be rejected at the 5% level. The insignificant coefficients or unexpected signs of some variables in the monetary and other models may pose some challenges in applications. First Publish Online: 09 Jun 2011